058 Serum neurofilament-light concentration and real-world outcome in MS. Issue 6 (27th May 2022) - Anderson, Valerie; Bentley, Emily; Loveless, Sam; Bianchi, Lucia; Harding, Katharine E; Thomas, Ray Wynford-; Giovannoni, Gavin; Robertson, Neil P; Marta, Monica; Tallantyre, Emma C
Abstract : Predicting clinical outcome in multiple sclerosis (MS) remains challenging, and biomarkers capable of providing prognostic information would be valuable in shaping therapeutic decisions. Neurofilament light (NfL) measurements have shown promise in predicting clinical outcomes in MS. We evaluated the relationship between serum NfL (sNfL), measured at diagnosis in 164 people with MS, with contemporary disability, short-term (1-year) and medium-term (5-year) clinical outcomes. Analyses were adjusted for relevant confounders. sNfL concentration at diagnosis was modestly but significantly associated with baseline EDSS score (B=0.264, 95% CI 0.043 to 0.485, p=0.020). However, no significant associations were found between baseline sNfL and the incidence of relapse at 12-months, time to sustained accumulation of disability or 5-year change in EDSS. Dichotomising baseline sNfL according to previously cited cut-offs (</> 14.2pg/ml and </> 90th percentile for age) did not change these results. sNfL appears to be of limited clinical utility in predicting future irreversible neurological disability, in a largely treated population, and remains insufficiently validated to shape treatment decisions at the time of diagnosis. Further studies exploring the value of sequential sNfL measurement and developing valid, universally accepted cut-offs are needed before sNfL can be incorporated as a prognostic marker in the clinic. tallantyreec@cardiff.ac.uk